Correction: Li et al. Environmental Simulation Model for Rapid Prediction of Tea Seedling Growth. Agronomy 2022, 12, 3165 - He Li; Yilin Mao; Yu Wang; Kai Fan; Hongtao Shi; Litao Sun; Jiazhi Shen; Yaozong Shen; Yang Xu; Zhaotang Ding (Agronomy)
The journal’s Editorial Office and Editorial Board are jointly issuing a resolution and removal of the Journal Notice linked to this article [...]